2018
DOI: 10.1038/s41893-018-0176-z
|View full text |Cite
|
Sign up to set email alerts
|

The global extent of biodiversity offset implementation under no net loss policies

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
138
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 153 publications
(146 citation statements)
references
References 37 publications
1
138
0
7
Order By: Relevance
“…We restricted our search to English‐language articles from relevant topic categories (Supporting Information). Previous research has shown that English captures most literature on offsets tied to international funding requirements, studies from North America and Oceania, and a substantial proportion of European literature, so our findings should be representative of the global literature (Bull & Strange, ; Bull et al., ). Additionally, we searched through all reference lists in papers meeting our inclusion criteria for additional literature.…”
Section: Methodsmentioning
confidence: 71%
See 4 more Smart Citations
“…We restricted our search to English‐language articles from relevant topic categories (Supporting Information). Previous research has shown that English captures most literature on offsets tied to international funding requirements, studies from North America and Oceania, and a substantial proportion of European literature, so our findings should be representative of the global literature (Bull & Strange, ; Bull et al., ). Additionally, we searched through all reference lists in papers meeting our inclusion criteria for additional literature.…”
Section: Methodsmentioning
confidence: 71%
“…Twenty‐nine studies met our inclusion criteria (7% of potentially relevant studies), with a further three identified via in‐article citations, leaving 32 studies from five countries (Table ; Figure ). Our database includes four landscape‐scale, 18 program‐scale, and 10 project‐scale studies (covering 26 projects), and accounts for a minimum of 300,000 ha of offsets and 180,000 ha of impacts, representing approximately 2% of the global area of spatially explicit known offset implementation (Bull & Strange, ). In total, we identified 121 outcome variables (column 11, Table ) from 48 NNL policies or individual offsets (1–44 outcomes per study, mean = 3.75).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations